Is There Value-Added from the Review Process in Economics?: Preliminary Evidence from Authors - Laband, David N. (Quarterly Journal of Economics, 1990)
Do referees employed by journals merely screen acceptable from unacceptable manuscripts or are they charged with an additional value-adding responsibility vis-à-vis the papers they review? Drawing from editorial correspondence provided by survey respondents, I address this question by examining the relationship between citations of published papers and comments provided by reviewers and editors. Referees' comments demonstrate a positive impact on subsequent citation of papers, while comments made by editors show no such impact. Value-adding by editors appears to derive principally from efficient matching of papers with reviewers.